(untitled) (Research, Society and Development, 2021)
In this work, the influence of the conditions of preparation of lemongrass tea preparation on the chemical profile of the specified herbal medicine was investigated. To this end, the form of storage of the leaves and the methodology used during the process of extraction by infusion and decoction were varied, applying factorial planning and statistical analysis. Two matrices were built, for analysis relating: the use of fresh vegetable, dry or refrigerated with the type of extraction used, in which the contact time between the vegetable material and boiling water was varied. An analysis of the extracts involved dispersive liquid-liquid microextraction, followed by gas chromatography coupled with mass spectrometry. Data processing indicated that there is no difference in the use of dry or fresh leaves, while the use of leaves stored for 7 days in a refrigerator lead to extracts depleted in phytopharmaceuticals. Infusions performed without and with the aid of ultrasonication dissipate similar capacity. The decoction led to extracts with the presence of epoxidized metabolites. The longer the contact time between solvent and plant material, the higher the levels of extracted bioactive compounds. Subsequently, a matrix for univariate study was constructed, varying the extraction time between 5 and 65 minutes, in order to determine the maximum extraction point. It is concluded that the methodology that guarantees the extraction of bioactive terpenes in greater proportion and the absence of oxidized, non-phytotherapic products is the infusion of dry or fresh lemon grass leaves, where these and boiling water remain in contact for a period of 25 minutes.